Pemanfaatan Tiktok Sebagai Platform Digital Marketing Dalam Upaya Peningkatan Penjualan CV Avero Indonesia - Salsabila, Adisty Syifa; Soebiyantoro, Ugy (ProBisnis : Jurnal Manajemen, 2025)
The development of digital technology has significantly changed product marketing patterns. This study aims to analyze the use of TikTok as a digital marketing platform in an effort to increase sales of CV Avero Indonesia. The research method used is a case study with a qualitative and quantitative approach, collecting data through observation, interviews, and sales documentation. The results of the study show that promotional strategies through TikTok, such as creating creative content, using influencers, and actively interacting with consumers, have a positive impact on increasing product awareness and sales. In addition, the TikTok algorithm that facilitates the distribution of content organically expands market reach effectively. Thus, TikTok is proven to be an effective digital promotional media to increase product sales at CV Avero Indonesia. This study contributes to business actors who want to optimize digital marketing through social media.